Research and Education Networks: Putting Value into the Links - Kunda, Douglas; Khunga, Bonny (My University, 2015)
In Zambia over the last four years we have concentrated on creating a National Research and Education Network which can connect our education and research institutions within the country, and the rest of the world. Indeed, affordable and reliable Broadband connectivity has been our cry. Not long ago, Africa was spending in excess of US$70 million per annum for capacity of less than 1Gbp. Zambia in particular, as late as 2012, bandwidth tariffs was averaging US$4,500 per 1 Mbps per month compared to under US$30 in Belgium. Under these circumstances, it was extremely uneconomical for our universities and research institutions to really engage in inter-institutional research collaboration and benefit from opportunities that the Internet had opened up in Europe, the Americas and Far East. Furthermore, the prohibitive Bandwidth costs were a sleep-hold grip to science-driven research that could have been undertaken using the few High Performance Computers on the continent. The NRENs have been a game-changer in driving the cost of connectivity downwards to now average between US$100 to US$200 per 1Mbps per month. However, low cost Bandwidth alone cannot sustain NRENs growth. There is the need for NRENs to offer other value-added ICT services to research and education institutions which cannot be commercially offered by Commercial ISPs. In this paper, the authors address some services that emerging NRENs can implement and offer to their member institutions and highlight some strategic factors that can be considered. The paper also analyses sustainability strategies that high-end NRENs in Europe have implemented in order to remain viable.
Keywords: Research and Education Networks; NREN Services; eduroam; FID; Direct Research Assistance; High Performance Computers; ZAMREN; End-to-end Connectivity; Training and Support; Data; Public and Private Partnerships.